Additive prognostic impact of the cerebrospinal fluid arginine/ornithine ratio to established clinical scores in aneurysmal subarachnoid hemorrhage - Weller, Johannes; Lampmann, Tim; Asoglu, Harun; Schneider, Matthias; Ehrentraut, Stefan Felix; Lehmann, Felix; Güresir, Erdem; Dorn, Franziska; Petzold, Gabor C.; Vatter, Hartmut; Zimmermann, Julian (Frontiers in Neurology, 2023)
Cerebrospinal fluid (CSF) metabolites are increasingly recognized as prognostic factors in aneurysmal subarachnoid hemorrhage (SAH). The CSF arginine/ornithine ratio (Arg/Orn) was shown to predict cerebral vasospasms and clinical outcome in SAH. The additive prognostic value of Arg/Orn over established prognostic scores has not been investigated. CSF Arg/Orn and the established prognostic scores SAH, FRESH, SAH-PDS, HAIR, Rosen–McDonald, Hunt and Hess, WFNS and modified Fisher scale were determined in a prospective cohort of patients with aneurysmal SAH. Logistic regression models to predict a favorable outcome, defined as a modified Rankin Scale score of 0–3 at 3 months follow-up, were constructed for each score, both with and without the addition of Arg/Orn. The impact of Arg/Orn was assessed comparing logistic regression models containing the respective score with and without Arg/Orn with the likelihood ratio chi-squared test. CSF Arg/Orn and clinical scores were determined in 38 SAH patients. Arg/Orn was an independent predictor of clinical outcome when added to established prognostic scores (p < 0.05) with the exception of HAIR (p = 0.078). All models were significantly improved if Arg/Orn was added as a covariable (p < 0.05). The results of this study confirm Arg/Orn as an independent prognostic factor and its addition improves established prognostic models in SAH.